Trophoblasts, invasion, and microRNA - Doridot, Ludivine; Miralles, Francisco; Barbaux, Sandrine; Vaiman, Daniel (Frontiers in Genetics, 2013)
MicroRNAs (miRNAs) have recently become essential actors in various fields of physiology and medicine, especially as easily accessible circulating biomarkers, or as modulators of cell differentiation. To this respect, terminal differentiation of trophoblasts (the characteristic cells of the placenta in Therian mammals) into syncytiotrophoblast, villous trophoblast or extravillous trophoblast constitutes a good example of such a choice, where miRNAs have recently been shown to play an important role. The aim of this review is to provide a snapshot of what is known today in placentation mechanisms that are mediated by miRNA, under the angles of materno-foetal immune dialogue regulation, trophoblast differentiation and angiogenesis at the materno-foetal interface. Also, two aspects of regulation of these issues will be highlighted: the part played by oxygen concentration and the specific function of imprinted genes in the developing placenta.